Deep level defects and their instability in PLD-grown IGZO (In2Ga2Zn5O11) thin films studied by thermally stimulated current spectroscopy. (28th October 2020) - Wang, Buguo; Look, David; Anders, Jason; Leedy, Kevin; Schuette, Michael
Abstract: InGaZnO (IGZO) is an excellent semiconductor material for thin-film transistors (TFTs) used in direct-current and radio-frequency (RF) switching applications, especially since it can be grown at low temperatures on a wide variety of substrates. IGZO thin films with a composition of InGaZnO4 have been deposited and used as channel layers in TFTs for many applications to date; however, IGZO compositions can also be easily changed to vary their properties. These different compositions of IGZO may have different defect properties. In this study, we report the growth of IGZO with composition of In2 O3 :Ga2 O3 :5ZnO (In2 Ga2 Zn5 O11 ) by pulsed laser deposition (PLD) and its electronic defects studied by thermally stimulated current (TSC) spectroscopy. It was found that the as-grown sample has a DC activation energy of 0.62 eV, and four major traps with activation energies between ∼0.16–0.50 eV and one at ∼0.90 eV. Electrical properties and the deep traps of PLD-grown IGZO thin film were found to be varied by post-processing conditions such as thermal history and measurement conditions such as the bias and light exposure applied to the samples. The instabilities induced by these conditions can be explained by structural and stoichiometric features—the ZnO4 tetrahedra and GaO6 octahedra in the structure may become distorted, caused by oxidation or reduction, so that the different defect states could be changed and/or lattice energy variations from the distortion can be observed. This work demonstrates that current-based trap emission, such as that associated with TSC, can effectively reveal electronic defects in highly-resistive semiconductor materials, especially those that are not amenable to capacitance-based techniques, such as deep-level transient spectroscopy, and provide an effective manner to study the trap instabilities in IGZO.